2020
DOI: 10.1039/d0ta00509f
|View full text |Cite
|
Sign up to set email alerts
|

Cu/M:ZnO (M = Mg, Al, Cu) colloidal nanocatalysts for the solution hydrogenation of carbon dioxide to methanol

Abstract: Doped-ZnO nanoparticles, capped with dioctylphosphinate ligands, are synthesised by the controlled hydrolysis of a mixture of organometallic precursors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 93 publications
0
7
0
Order By: Relevance
“…Ablation of the Cu plate at 355, 532, and 1064 nm in propionitrile and butyronitrile led to the formation of Cu NPs. The peaks at 43.2° and 50.4° were consistent with face-centered cubic copper NPs (JCPDS #01-085-1326) 21 . These peaks coincided with the diffraction of the (111) and (200) planes, respectively.…”
Section: Resultsmentioning
confidence: 70%
“…Ablation of the Cu plate at 355, 532, and 1064 nm in propionitrile and butyronitrile led to the formation of Cu NPs. The peaks at 43.2° and 50.4° were consistent with face-centered cubic copper NPs (JCPDS #01-085-1326) 21 . These peaks coincided with the diffraction of the (111) and (200) planes, respectively.…”
Section: Resultsmentioning
confidence: 70%
“…This approach involves neither a purification step, nor corrosive byproducts, it operates at low temperature, is fast and ensures a quantitative yield of well‐defined NPs. [ 37 , 38 , 39 , 40 ] The formation of ZnO NPs by this approach is highly appealing as ZnO NPs present wide technological applications due to their unique properties. These include electro‐optical properties, [ 41 , 42 ] which can be used in devices such as ultraviolet (UV) light‐emitting diodes (LEDs), [ 42 , 43 ] blue luminescent devices or UV lasers [ 44 ] ; photo(electro)catalytic water treatment, [ 45 , 46 , 47 ] antibacterial agents, [ 48 , 49 ] solar cells, [ 50 , 51 , 52 , 53 , 54 ] and others.…”
Section: Resultsmentioning
confidence: 99%
“…[ 17 , 18 , 19 , 20 ] Although some publications report low toxicity for ZnO NPs, [ 21 , 22 ] the insecure handling of NPs before any further process implementations comprising the direct application, is currently encountered in classical processes like chemical precipitation, sol‐gel, solvothermal/hydrothermal methods, microemulsion and synthesis from organometallics precursors. [ 23 , 24 , 25 , 26 , 27 , 28 ] The development of processes that avoid contact with NPs remains therefore highly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 The properties of these materials can be modulated using promoters 6,7 and applying different synthesis methods. 8,9 Promoters, such as Fe, 10 Ga, 10,11 Mg, 12 Al, 12 and In, 13 can increase the dispersion of Cu, maximizing interface sites and the basicity, raising the CO 2 adsorption, while the synthesis method influences the morphology and structure of the catalysts, 14−16 allowing the optimization of the methanol generation.…”
Section: Introductionmentioning
confidence: 99%
“…In these processes, a wide variety of value-added chemicals can be obtained. In particular, methanol is an interesting product of catalytic CO 2 hydrogenation, owing to its broad range of applications. Previous studies showed that Cu/ZnO-based materials are promising for large-scale methanol production from CO 2 and H 2 . , The properties of these materials can be modulated using promoters , and applying different synthesis methods. , Promoters, such as Fe, Ga, , Mg, Al, and In, can increase the dispersion of Cu, maximizing interface sites and the basicity, raising the CO 2 adsorption, while the synthesis method influences the morphology and structure of the catalysts, allowing the optimization of the methanol generation.…”
Section: Introductionmentioning
confidence: 99%